2003
DOI: 10.1002/ps.751
|View full text |Cite
|
Sign up to set email alerts
|

Association of MACE‐based insecticide resistance in Myzus persicae with reproductive rate, response to alarm pheromone and vulnerability to attack by Aphidius colemani

Abstract: Reproductive success and response to alarm pheromone, both potentially important components of fitness, were assessed using clones of Myzus persicae (Sulzer) to establish associations with insecticide resistance conferred by insensitive modified acetylcholinesterase (MACE). Both traits showed significant trends that were apparently related to this mechanism. MACE forms appeared to reproduce at slower rates than non-MACE forms expressing moderate (R1) levels of another resistance mechanism based on elevated car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
2
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 25 publications
(33 reference statements)
3
33
2
1
Order By: Relevance
“…Pleiotropic effects of E4/FE4 gene duplication and kdr mutation on important behavioral traits have been reported for M. persicae , particularly in response to environmental signals such as presence of natural enemies (parasitoids) and low temperatures, which ultimately could lead to reduced fitness [58][63]. In addition, the MACE mutation appears to reduce the fitness of individuals that carry it [64]. However, the effect of this mutation by itself has not been clarified yet [65], [66].…”
Section: Discussionmentioning
confidence: 99%
“…Pleiotropic effects of E4/FE4 gene duplication and kdr mutation on important behavioral traits have been reported for M. persicae , particularly in response to environmental signals such as presence of natural enemies (parasitoids) and low temperatures, which ultimately could lead to reduced fitness [58][63]. In addition, the MACE mutation appears to reduce the fitness of individuals that carry it [64]. However, the effect of this mutation by itself has not been clarified yet [65], [66].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in highly resistant clones of Myzus, changes in DNA methylation were also shown to be able to switch off the high levels of E 4 production associated with highly duplicated E 4 -encoding genes, thereby presumably reducing the energetic cost of having to make a large amount of esterase in the absence of pesticide (Field et al 1989b). The idea that only carboxylesterase-associated gene duplication could cause resistance persisted until 1990 when both insensitive acetylcholinesterase and altered voltage-gated sodium channels (kdr) were also shown to be involved in resistance to organophosphorus/carbamates and pyrethroids, respectively (MartinezTorres et al 1999;Foster et al 2003). In fact, retrospective surveys of the three resistance mechanisms in the United Kingdom actually showed that their relative frequencies had in fact been changing over time (Field and Foster 2002), suggesting that some mechanisms may show increased levels of fitness (in the absence of pesticide) or efficacy (in the presence of pesticide) over others.…”
Section: Multiple Mechanisms Within a Single Genome: Aphids And Estermentioning
confidence: 99%
“…Myzus persicae clones with high levels of esterase have maladaptive behaviour affecting their ability to overwinter ( Foster et al , 1996( Foster et al , , 1997 whereas clones with the kdr gene are known to be less responsive to alarm pheromones, which may affect their ability to respond to unfavourable conditions (e.g. over crowding, poor plant nutrition, predation and parasitism; Foster et al , 1999Foster et al , , 2003Foster et al , , 2005.…”
Section: Persicae Populationmentioning
confidence: 99%